2000
DOI: 10.1155/s1110662x0000012x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and photoelectric studies of phthalocyanines in polyvinyl alcohol for application in solar energy conversion

Abstract: Abstract. Phthalocyanines are synthetic dyes which are shown to be good photoconverters which can be applied in a photoelectrochemical cell constructed of semiconducting and metallic electrodes. By means of spectroscopic investigation (absorption, fluorescence and photoacoustics) we have followed spectral properties of phthalocyanines complexed with metals dissolved in polyvinyl alcohol solution in order to determine the pathways of deactivation of their excited states. Spectroscopic investigations were accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[9] The dyes in aqueous PVA show similar photocurrent kinetics to those observed for porphyrins and phthalocyanines. [10][11][12] Along with the increasing number of applications for photoactive films, a need has arisen for methods to fabricate devices consisting of functional polymer microstructures that are spatially patterned in the plane of a substrate. Our studies in this field were initiated with a photochemical investigation of t-BOC-protected quinizarin polymer for fluorescent imaging, in which we showed that thin films of t-BOC-protected quinizarin undergo photoinduced deprotection and solubilization upon exposure to UV-vis light.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The dyes in aqueous PVA show similar photocurrent kinetics to those observed for porphyrins and phthalocyanines. [10][11][12] Along with the increasing number of applications for photoactive films, a need has arisen for methods to fabricate devices consisting of functional polymer microstructures that are spatially patterned in the plane of a substrate. Our studies in this field were initiated with a photochemical investigation of t-BOC-protected quinizarin polymer for fluorescent imaging, in which we showed that thin films of t-BOC-protected quinizarin undergo photoinduced deprotection and solubilization upon exposure to UV-vis light.…”
Section: Introductionmentioning
confidence: 99%
“…The 60 :m sample of dye in PVA was embedded in a sandwich-like construction of semiconducting (In 2 O 3 ) and gold (Au) electrodes [13]. The following measurements were made with the automatic Potentiostat-Galvanostat (Compex, Poland) apparatus: kinetics of photocurrent, current-voltage characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…In solutions which contain sensitisers, charge separation, electron acceptors and donors or energy transfer within the very short excitation time of the sensitizers occur [6]. In solid devices of organic photovoltaic cells electrical energy can be obtained [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…10 Among MPcs, zinc phthalocyanine (ZnPc) is an important organic semiconductor with a high absorption coefficient and good photochemical and thermal stabilities, which make it a suitable material for photovoltaic applications, gas sensors and optoelectronic devices. [11][12][13] The high performance of photovoltaic cells can be achieved by using semiconductors which convert sunlight into electricity, conductive oxides or transparent dielectrics as antireflection coatings. A high refractive index is the most common characteristic of these materials.…”
Section: Introductionmentioning
confidence: 99%